Manajemen Kurikulum Manajemen Kurikulum Berbasis Drill Di Sekolah Islam Dalam Menanamkan Nilai-nilai Spiritual Siswa - Ayu Umi Salamah; Ayu Wulandari; Syunu Trihantoyo; Amrozi Khamidi; Nur Aisyah; Faruq Abdul Muid (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2026)
The cultivation of students' spiritual values in Islamic schools requires curriculum management that not only organizes learning content, but also guides the internalization of moral values through meaningful habituation. This study aims to analyze the role of curriculum management functions, namely Planning, Organizing, Actuating, and Controlling (POAC), in instilling spiritual values consisting of moral knowing, moral feeling, and moral action among students through a drill-based curriculum. This research employed a Systematic Literature Review (SLR) using the PRISMA approach. Literature was searched in PubMed, Scopus, ScienceDirect, Taylor & Francis, Google Scholar, and SINTA with the keywords "Curriculum Management", "Drill Method", "Spiritual Values", "Character Education", "Tahfidz", and "Munaqosyah" for publications within the last ten years. From 180 initial records, 130 duplicates were removed, 50 articles were screened, 18 full-text articles were assessed, and 15 articles met the inclusion criteria for synthesis. The findings indicate that POAC-based curriculum management plays a significant role in connecting repetitive drill practices with students' spiritual internalization through systematic planning, clear role organization, reflective implementation, and continuous qualitative evaluation. The study concludes that drill-based curriculum management can support students' honesty, responsibility, and self-confidence when repetition is accompanied by meaning-making, teacher modelling, reflection, and authentic assessment.